Shaping of Flexible Metal‐Organic Frameworks: Combining Macroscopic Stability and Framework Flexibility. Issue 43 (4th November 2019) - Kriesten, Martin; Vargas Schmitz, Jürgen; Siegel, Jonas; Smith, Christopher E.; Kaspereit, Malte; Hartmann, Martin
Abstract : A facile extrusion approach that can fully retain the breathing behavior of flexible metal‐organic frameworks (MOF) like MIL‐53 and MIL‐53‐NH2 employing methyl cellulose as binder is reported. Shaped MOF extrudates were extensively characterized by nitrogen sorption, X‐ray diffraction, thermogravimetric analysis and scanning electron microscopy. A detailed study on the mechanical stability of MIL‐53 extrudates with different amounts of binder reveals an increase in stability at low binder fractions while the maximum in attainable stability is reached at 5 wt.‐% binder. In‐situ XRD studies in CO2 atmosphere and under humid conditions, respectively, demonstrate the reversibility in breathing behavior of the MIL‐53 extrudates without affecting the phase transition kinetics. High‐pressure methane and carbon dioxide isotherms on MIL‐53 and MIL‐53‐NH2 extrudates exhibit loadings that are comparable to the uptake of the pristine powder. The shaping approach reported herein paves the way for using flexible MOF structures in technical applications. Abstract : The flexible metal‐organic framework MIL‐53 has been shaped into cylindrical extrudates for technical applications. In situ XRD under non‐ambient conditions as well as high pressure CO2 adsorption isotherms demonstrate the structural flexibility of MIL‐53 in its extruded form. Furthermore, the mechanical stability of the MOF extrudates has been thoroughly studied.